Targeted messaging on livestock’s contribution to nutrition and livelihoods in developing countries provides a more balanced and inclusive perspective to the 2019 EAT Lancet Report - CGIAR Research Program on Livestock (2019)
The 2019 EAT Lancet Report introduced new global dietary guidelines that promote reduced consumption of animal source foods. In response, scientists from the CGIAR research programs on Livestock and Agriculture for Nutrition and Health (A4NH) synthesized and promoted evidence on the contribution of livestock to human nutrition and livelihoods in developing countries, highlighting the need for more inclusive dietary recommendations. Global discussions were also influenced by an op-ed by a senior official from Ethiopia’s Ministry of Agriculture developed with ILRI.